2020
DOI: 10.1007/s12193-020-00322-2
|View full text |Cite
|
Sign up to set email alerts
|

Movement sonification expectancy model: leveraging musical expectancy theory to create movement-altering sonifications

Abstract: When designing movement sonifications, their effect on people's movement must be considered. Recent work has shown how real-time sonification can be designed to alter the way people move. However, the mechanisms through which these sonifications alter people's expectations of their movement is not well explained. This is especially important when considering musical sonifications, to which people bring their own associations and musical expectation, and which can, in turn, alter their perception of the sonific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…This is in-line with new theories of emotional experience, seeing emotions as concepts constructed by multiple brain processes and shaped by factors that characterize people's previous experiences and needs [1]. As such it is important to study not just the common patterns but the variability to better understand the factors that contribute to the effects of sonification that started to emerge in [23,42].…”
Section: Linking Effects On Body/movement Perception and Pasupporting
confidence: 56%
“…This is in-line with new theories of emotional experience, seeing emotions as concepts constructed by multiple brain processes and shaped by factors that characterize people's previous experiences and needs [1]. As such it is important to study not just the common patterns but the variability to better understand the factors that contribute to the effects of sonification that started to emerge in [23,42].…”
Section: Linking Effects On Body/movement Perception and Pasupporting
confidence: 56%
“…For example, post-surgery physical rehabilitation patients or beginner yoga practitioners, might be happy with a simple lower your arms'-type of verbal feedback [602,661], while others might nd it strenuous and needlessly ambiguous [282]. Correctly executed exercise could be rewarded with a simpler auditory feedback such as a click [215], or by a movement sonication such as experimented in physical rehabiliation [579,711], or with music feedback that was shown recently to improve deadlift technique [499]. In sEMG studies, it was shown tha tfocused verbal feedback had a positive impact on activating triceps brachii more than without feedback [249,604], highlighting the need of some human oversight and encouragement [565,852].…”
Section: B Real-time Feedback Methodsmentioning
confidence: 99%
“…Effects of harmonic content (stability of musical sounds) on bodily movement: Musically resolved (i.e., ending on a perfect or harmonically stable cadence) vs. unresolved (i.e., ending on an imperfect or harmonically unstable cadence) sonifications accompanying arm raise movements lead people to increase the movement amplitude and stretch for longer, potentially due to musical expectation [35].…”
Section: Bodily Movement Movement Parametersmentioning
confidence: 99%
“…-Effects of harmonic content: Musically resolved sonifications accompanying stretching and squat movements increase feelings of reward and achievement, as well as motivation to continue the movement [35,40,51].…”
Section: Effects Of Change On Pitch On Bodily and Emotional Feelingsmentioning
confidence: 99%